Svar:
Se nedenfor.
Forklaring:
#f (x) = x ^ 5-4x ^ 4 + 3x 3x ^ ^ 2 + 12 #
#f (x) = x ^ 5-2x ^ 4-2x ^ 4 + 4x ^ 3-x ^ 3 + 2x ^ 2-3 x ^ 2 + 12 #
#f (x) = x ^ 4 (x-2) -2x ^ 3 (x-2) -X ^ 2 (x-2) -3 (x ^ 2-4) #
#f (x) = x ^ 4 (x-2) -2x ^ 3 (x-2) -X ^ 2 (x-2) -3 (x-2) (x + 2) #
#f (x) = x ^ 4 (x-2) -2x ^ 3 (x-2) -X ^ 2 (x-2) - (3x + 6) (x-2) #
Nå kan vi faktor # (X-2) # ute:
#f (x) = (x-2) (x ^ 4-2x ^ 3-x ^ 2-3 x-6) Antall
Du kan også løse dette problemet ved å utføre en lang deling av #f (x) # av # x-2 #.